Proton‐Pump Inhibitors and Long‐Term Risk of Community‐Acquired Pneumonia in Older Adults. Issue 7 (20th April 2018) - Zirk‐Sadowski, Jan; Masoli, Jane A.; Delgado, Joao; Hamilton, Willie; Strain, W. David; Henley, William; Melzer, David; Ble, Alessandro
Abstract : Objectives: To estimate associations between long‐term use of proton pump inhibitors (PPIs) and pneumonia incidence in older adults in primary care. Design: Longitudinal analyses of electronic medical records. Setting: England Participants: Individuals aged 60 and older in primary care receiving PPIs for 1 year or longer (N=75, 050) and age‐ and sex‐matched controls (N=75, 050). Measurements: Net hazard ratios for pneumonia incidence in Year 2 of treatment were estimated using the prior event rate ratio (PERR), which adjusts for pneumonia incidence differences before initiation of treatment. Inverse probability weighted models adjusted for 78 demographic, disease, medication, and healthcare usage measures. Results: During the second year after initiating treatment, PPIs were associated with greater hazard of incident pneumonia (PERR‐adjusted hazard ratio=1.82, 95% confidence interval=1.27–2.54), accounting for pretreatment pneumonia rates. Estimates were similar across age and comorbidity subgroups. Similar results were also obtained from propensity score– and inverse probability–weighted models. Conclusion: In a large cohort of older adults in primary care, PPI prescription was associated with greater risk of pneumonia in the second year of treatment. Results were robust across alternative analysis approaches. Controversies about the validity of reported short‐term harms of PPIs should not divert attention from potential long‐term effects of PPI prescriptions on older adults.